Comparación multitemporal de áreas quemadas en un bosque seco tropical utilizando el índice de área quemada (IAQ) - Vargas-Sanabria, Daniela (2020)
Post-fire analysis such as the burned area index (BAI) allows us to discriminate affected areas and the severity offires. In this study, the annual behaviour of the BAI was analyzed in the tropical dry forest region of the GuanacasteConservation Area, Costa Rica among 1997 to 2019 according to the frequency of fires. Our results show that theareas frequently burned by forest fires display a differentiated behaviour in the BAI throughout the years. Where,the greater the frequency of forest fires is, the higher the BAI values. On the other hand, areas that have not beenaffected or have been affected by a single fire showed low BAI values. These results could validate the hypothesisthat after two to three fires, the forest seed bank is destroyed. Consequently, the composition and structure oftropical dry forests change considerably after the occurrence of many fires.